2020
DOI: 10.3389/fpls.2020.563971
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Fruit Etiolation on Quality of Seeds in Tobacco

Abstract: Seed’s maturity and integrity are essential requirements for germination, and they rely on nutrients availability and a correct phytohormones’ balance. These aspects are prerequisites for prompt germination at the end of the dormancy period and strictly depend on chloroplast metabolism and photosynthesis. In the present work, capsules of Nicotiana tabacum were grown in dark during the whole post-anthesis period. Among others, photosynthetic rates, dormancy, and phytohormones levels in se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 45 publications
5
8
0
Order By: Relevance
“…The readout of this assessment was performed by analyzing the seed quality in terms of the germination kinetics of seeds collected from both photomorphogenetic capsules (PC) and skotomorphogenetic capsules (SC). While SC seeds had an almost absent dormancy with no significant differences between the three conditions tested, consistent with previous studies performed under white light in N. tabacum L. [28], seeds developed in PC presented different behaviors depending on the type of light under which the seed maturation occurred. In particular, PC seeds from capsules developed under white and red light showed a clear dormancy phase, while, unexpectedly, in PC seeds from capsules developed under blue light, the dormancy was absent, showing a skotomorphogenetic-like behavior.…”
Section: Introductionsupporting
confidence: 91%
See 3 more Smart Citations
“…The readout of this assessment was performed by analyzing the seed quality in terms of the germination kinetics of seeds collected from both photomorphogenetic capsules (PC) and skotomorphogenetic capsules (SC). While SC seeds had an almost absent dormancy with no significant differences between the three conditions tested, consistent with previous studies performed under white light in N. tabacum L. [28], seeds developed in PC presented different behaviors depending on the type of light under which the seed maturation occurred. In particular, PC seeds from capsules developed under white and red light showed a clear dormancy phase, while, unexpectedly, in PC seeds from capsules developed under blue light, the dormancy was absent, showing a skotomorphogenetic-like behavior.…”
Section: Introductionsupporting
confidence: 91%
“…The influence of phytochromes on seed dormancy, affecting hormone biosynthesis, levels, and balance, is also taken into account. Considering previous observations [28], the reported data may have relevant applications in crop production or plant preservation for species where, as in tobacco, etiolation of fruits induces bigger and heavier seeds with reduced dormancy.…”
Section: Introductionsupporting
confidence: 56%
See 2 more Smart Citations
“…Therefore, our objective was to characterize seed morphology and weight, considering their ecological and functional importance. Preliminary microscopical observations, together with the scientific literature on the topic, suggested that seeds may differ among the two studied populations depending on the peculiar growth conditions characterizing one of them (PPS) [ 16 , 24 , 25 , 26 , 27 ]. To characterize seeds produced by PPS, a second population of the same species geographically close, and sharing the same climatic and ecological conditions (except for the soil pollution), was chosen for comparison (PCS hereafter, which stands for “plants growing on the control site”).…”
Section: Introductionmentioning
confidence: 99%